2004
DOI: 10.1074/jbc.m313363200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Natures of Beryllium Fluoride-bound, Aluminum Fluoride-bound, and Magnesium Fluoride-bound Stable Analogues of an ADP-insensitive Phosphoenzyme Intermediate of Sarcoplasmic Reticulum Ca2+-ATPase

Abstract: The structural natures of stable analogues for the ADP-insensitive phosphoenzyme (E2P) of Ca 2؉ -ATPase formed in sarcoplasmic reticulum vesicles, i.e. the enzymes with bound beryllium fluoride (BeF⅐E2), bound aluminum fluoride (AlF⅐E2), and bound magnesium fluoride (MgF⅐E2), were explored and compared with those of actual E2P formed from P i without Ca 2؉ . Changes in trinitrophenyl-AMP fluorescence revealed that the catalytic site is strongly hydrophobic in BeF⅐E2 as in E2P but hydrophilic in MgF⅐E2 and AlF⅐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
116
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(134 citation statements)
references
References 71 publications
18
116
0
Order By: Relevance
“…6). Intrinsic Trp fluorescence levels substantiate this finding (28). The fluorescence of E2⅐MgF 4 2Ϫ is low and similar to that of E2(TG), and the difference between E2 and E2P is likely to reflect the environment of Trp-288 at the bottom of M4, because this is the most prominent change among the transmembrane helices between these two structures.…”
Section: Discussionsupporting
confidence: 62%
“…6). Intrinsic Trp fluorescence levels substantiate this finding (28). The fluorescence of E2⅐MgF 4 2Ϫ is low and similar to that of E2(TG), and the difference between E2 and E2P is likely to reflect the environment of Trp-288 at the bottom of M4, because this is the most prominent change among the transmembrane helices between these two structures.…”
Section: Discussionsupporting
confidence: 62%
“…There is particular interest in the origin of the superfluorescence of TNP-AMP in the E2P ground state. E2 · BeF 3 − is a stable analogue of the E2P ground state, and superfluorescence is observed even in the presence of TG (25). This is in marked contrast to E2 · AlF 4 − , a stable transition state analogue, in which TNP-AMP exhibits little fluorescence (25).…”
Section: Resultsmentioning
confidence: 59%
“…E2 · BeF 3 − is a stable analogue of the E2P ground state, and superfluorescence is observed even in the presence of TG (25). This is in marked contrast to E2 · AlF 4 − , a stable transition state analogue, in which TNP-AMP exhibits little fluorescence (25). Hence we soaked TNP-AMP into E2 · BeF 3 − ðTGÞ and E2 · AlF 4 − ðTGÞ crystals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the K + counter-transport pumps E 2 P must allow for both the escape of the outward moving ion (sodium or hydronium) and for the passage of luminal K + to the ion occlusion site. There is no open path in the PDB 1wpg structure from the ion site to the lumen, however, and it has been suggested that this structure represents the product-bound state, E 2 ·P, in which Ca 2+ has been released to the lumen, the ion sites have incorporated protons for counter transport, and the luminal gate has been closed (34). Nevertheless, the PDB 1wpg form has bound MgADP which is associated with an expanded luminal vestibule compared to the previously published E 2 conformation (PDB code 1iwo).…”
mentioning
confidence: 99%